2006
DOI: 10.1002/jcp.20914
|View full text |Cite
|
Sign up to set email alerts
|

CMTM8 induces caspase‐dependent and ‐independent apoptosis through a mitochondria‐mediated pathway

Abstract: The mitochondria-mediated apoptotic pathway is regulated by members of the Bcl-2 family. Epidermal growth factor (EGF) induces Bad phosphorylation at Ser112 via mitogen-activated protein kinase (MAPK), impairing its binding to Bcl-2 and Bcl-xL and interfering with their anti-apoptotic functions. In the current study, we utilized Western blot, immunofluorescence, flow cytometry, and confocal microscopy to examine the effects of CMTM8 overexpression on apoptosis. Our data indicated levels of Bad-S112 phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…At indicated time points, the cells were harvested, washed with cold phosphate-buffered saline (PBS) and re-suspended in 200 μL of binding buffer (10 mmol/L HEPES, 140 mmol/L NaCl, 2 mmol/L MgCl 2 , 5 mmol/L KCl, 2.5 mmol/L CaCl 2 , pH 7.4) containing Annexin-V-FITC (25 μg/mL). After incubation for 20-30 min at room temperature in the dark, 5 μL PI (1 μg/mL) was added and samples were immediately analyzed with a FACSCalibur flow cytometer (Becton Dickinson, Franklin Lakes, NJ) [28] . For each sample, 1×10 4 cells were collected and analyzed with CellQuest software (Becton Dickinson).…”
Section: Detection Of Phosphatidylserine (Ps) Externalizationmentioning
confidence: 99%
“…At indicated time points, the cells were harvested, washed with cold phosphate-buffered saline (PBS) and re-suspended in 200 μL of binding buffer (10 mmol/L HEPES, 140 mmol/L NaCl, 2 mmol/L MgCl 2 , 5 mmol/L KCl, 2.5 mmol/L CaCl 2 , pH 7.4) containing Annexin-V-FITC (25 μg/mL). After incubation for 20-30 min at room temperature in the dark, 5 μL PI (1 μg/mL) was added and samples were immediately analyzed with a FACSCalibur flow cytometer (Becton Dickinson, Franklin Lakes, NJ) [28] . For each sample, 1×10 4 cells were collected and analyzed with CellQuest software (Becton Dickinson).…”
Section: Detection Of Phosphatidylserine (Ps) Externalizationmentioning
confidence: 99%
“…5 The longer isoform promotes EGF receptor (EGFR) internalization and attenuates EGFR-mediated signaling for cell growth (29). When overexpressed, both isoforms induce apoptosis in multiple tumor cell lines (30,31). In this work, unless specifically described, CMTM8 refers to both isoforms.…”
mentioning
confidence: 99%
“…Etoposide was also found to induce caspase-8 processing and apoptosis in a CD95-independent fashion because blocking of CD95 receptor function with a specific antibody does not inhibit etoposide-induced apoptosis [38]. Jin et al 2007 showed cancer cell lines transfected with chemokine-like factor CMTM8 submit to apoptosis. Caspase-dependent and independent mediated apoptosis, induced by CMTM8 overexpression, was facilitated by the mitochondria and inhibited by knockdown of Bad or overexpression of Bcl-xL [39].…”
Section: Signaling Pathways Of Apoptosismentioning
confidence: 99%
“…Jin et al 2007 showed cancer cell lines transfected with chemokine-like factor CMTM8 submit to apoptosis. Caspase-dependent and independent mediated apoptosis, induced by CMTM8 overexpression, was facilitated by the mitochondria and inhibited by knockdown of Bad or overexpression of Bcl-xL [39].…”
Section: Signaling Pathways Of Apoptosismentioning
confidence: 99%